A two-weight estimate for a class of fractional integral operators with rough kernel - Yong Ding (International Journal of Mathematics and Mathematical Sciences)
We prove that the operators in a class of rough fractional integral operators and the related maximal operators are bounded from Lp(vp) to Lq(uq) with weight pair (u,v).